Examination of Relationships of Scores Obtained in Grades 10 and 12 with the Entry and Success in Undergraduate Medical Education - Gautam, AP; Paudel, BH; Agrawal, CS; Naraula, SR; Dalen, J Van (Kathmandu University Medical Journal, 2012)
Background Entrance examination (admission test) is the most important and widely accepted method of student selection for admission into medical schools in Nepal. For many schools it is the only criterion of student selection. Objectives To examine relationships of scores obtained in schooling (grade 10 and 12), medical entrance and MBBS professional examinations in a cohort to identify predictive strength for entry into medical school and success in medical education. Methods Exam scores from grade 10 to medical entrance and professional exams of undergraduate medical education of a total of 118 medical students who entered medical school between 1994 and 1998 only through the merit of open competitive medical entrance examination at the BP Koirala Institute of Health Sciences (BPKIHS) were assessed. Results Student selection for admission in MBBS course at BPKIHS and their subsequent success were not determined by difference in outcomes of public & private management of schools at grade 10 (selection p= 0.80 & success p= 0.32 ) and grade 12 (selection p= 0.59 & success p= 0.55). Grade 12 averaged scores had no relationship in getting these students selected for admission into medical course (r= 0.08, p= 0.37), but did show correlation with the overall success in medical education (r= 0.32, p= 0.00). Scores in physics at grade 12 retained predictive strength in success in medical education (r= 0.19, p= 0.04). Conclusion The present student selection criteria for medical education are not appropriate and need to incorporate other attributes of candidates along with cognitive aspects. KATHMANDU UNIVERSITY MEDICAL JOURNAL VOL.10 | NO. 1 | ISSUE 37 | JAN - MAR 2012 | 66-71 DOI: http://dx.doi.org/10.3126/kumj.v10i1.6918